Badiou : A Subject To Truth - Hallward, Peter (Book collections on Project MUSE., 2003)
Badiou is the first comprehensive introduction to Alain Badiou's thought to appear in any language; it provides a highly readable discussion of each of the basic features of his ontology. Peter Hallward demonstrates in detail and in depth why Badiou's ongoing philosophical project should be recognized as the most resourceful and inspiring of his generation.